Desonida: validação de métodos analíticos e estudo de fotoestabilidade de formulações - Braga, Muriele Picoli (2013)
Desonide is a nonfluorinated corticosteroid with glucorticoid activity. It is used topically in the treatment of atopic dermatitis, inflammation, pruritus and seborrheic dermatitis of mild to moderate severity. In Brazil, this drug is available as ointment, cream, lotion, hair lotion and cream gel. Until now, there are no official methods focused in the quality control of desonide raw material or its pharmaceutical forms. In this work, methods were developed and validated by high performance liquid chromatography (HPLC) for quantitation of desonide in lotion and cream gel. Furthermore, photostability studies of these formulations were conducted. The HPLC methods were validated by parameters of linearity, precision, accuracy, robustness and specificity, which results showed that both methods are stability-indicating. Chemometric tools were used to study the robustness of the proposed methods (desonide lotion and cream gel) and also for the optimization of chromatographic conditions (cream gel). Photostability studies were conducted with an equivalent procedure, by exposure to UVA radiation (352 nm) portions of the samples for a period of 48 h. The results showed that both formulations undergo photodegradation, and the lotion exhibits a degradation rate greater than the cream gel (t90% 1.58 h for the lotion and 3.65 h for the gel). The study of the kinetics of the reactions indicated that lotion follows second-order kinetics, while the cream gel follows first order kinetics.